Point prevalence of antimicrobial prescriptions among inpatient in a tertiary level hospital in Nepal - Karki, Arjun; Shrestha, Anmol Purna; Shrestha, Abha; Shrestha, Rajeev; Shrestha, Roshana (Journal of General Practice and Emergency Medicine of Nepal, 2021)
Introduction: Inappropriate use of antimicrobials increases resistance, morbidity, and mortality. Accurate information on the use of antibiotics is crucial to address the problem of antibiotic overuse and resistance. The aim of this study is to explore the antibiotic prescription pattern at inpatient departments of Dhulikhel Hospital. Method: This prospective point prevalence study was conducted in five inpatient departments by making 25 visits between June 2018 and March 2019. Patient planned to be discharged on the day of visit was included in the study. The details of the patients who received at least one antimicrobial for at least one clinical treatment condition or prophylaxis during the hospital stay was recorded. The data on the antimicrobials received, diagnosis, therapeutic indication according to predefined lists, and markers of prescribing quality were recorded. Result: Out of 179 patients, 125 patients (69.8%) were prescribed one or more antibiotics. There was noticeable variation in prevalence of antibiotic prescription across the departments, ranging from 59.5%-78.9 %. The top three prescribed antibiotics were third generation cephalosporins 63 (38%), broad spectrum penicillin 49 (29.5%), and metronidazole 19 (11.4%). The patients received antibiotic for non bacteriological proven infection 66 (52.8%) and only 8 (6.4%) patient received antibiotic for bacteriological proven infection. Culture and sensitivity testing were sent in 45(36%) patients and urine was the most frequent specimen Conclusion: Study concluded that there is need to further explore factors contributing to the high prevalence of antibiotic use and develop strategies for appropriate antibiotic use in the hospital.